A cohort study investigating medication management by pharmacists to prevent drug-related problems in pain therapy. Issue 3 (10th December 2014) - Schiek, Susanne; Hildebrand, Carolin; Ranft, Donald; Dürrbeck, Axel; Ghanem, Mohamed; von Salis-Soglio, Georg; Frontini, Roberto; Bertsche, Thilo
Abstract : Objectives: We aimed at identifying drug-related problems in pain therapy and assessed the effect of medication management by pharmacists in routine care. Methods: We performed a cohort study consisting of a control (no pharmaceutical service) and a medication management group receiving pharmaceutical services including recommendations to physicians. We defined pharmacotherapeutic and administrative drug-related problems in pain therapy and analysed patient charts to assess the outcomes. Active participants in the study were not involved in study assessment. Outcomes were the number of patients and the number of analgesic prescriptions with drug-related problems. Results: We analysed 414 medication records (controls: 208, medication management: 206). Our intervention had no influence on the number of patients with drug-related problems following analgesic prescriptions (control: 166/208, 80% vs medication management: 155/206, 75%, p=0.266). In 98 control group patients (47%), we found at least four drug-related problems. This fraction was smaller in the medication management group, with 66 patients (32%; p=0.002). The number of analgesic prescriptions leading to drug-related problems decreased from controls with 381/627 (61%) to 308/654 (47%) in the medication management group (p<0.001). Conclusions: Current pain therapy standards were not strictly adhered to in routine analgesic prescriptions for orthopaedic patients. The inclusion of pharmacists into the team successfully decreased drug-related problems. However, further interventions are required to achieve optimal effects.